ShanghaiGrid in action: the first stage projects towards digital city and city grid. (17th May 2005) - Li, Minglu; Liu, Hui; Tang, Feilong; Hong, Feng; Jiang, Changjun; Tong, Weiqin; Zhou, Aoying; Gui, Yadong; Zhu, Hao; Jiang, Shui
The nearest goal of ShanghaiGrid is going to connect all supercomputers in this metropolis together to form a sharing environment for massive storage and grid computing. The first stage projects of ShanghaiGrid comprise four sub-projects, including: research on environment, protocols and standards of information grid infrastructure; development of system software for information grid and establishment of four major intra-grid nodes; development of peer-to-peer based virtual research platform; research on the application of grid based traffic-jam control and guidance. This paper introduces the background of ShanghaiGrid, provides a glimpse at features and challenges of its sub-projects, and summarises the general goal of them.